Reward and Punishment: Student Discipline Solutions? - Aliya Maulida; Anisa Nurshiffa Awalia; Ridha Nur Fauziah; Imam Tabroni (Acta Psychologia, 2022)
Research this background with implementation reward method and punishment applied in the Tahfidz Raudhatul Qur'an Modern Pondok as effort increase discipline and achievement, method this suitable used because can give effect like and wary however on in fact part big santri discipline and achievement still low. study this aim: to explain implementation, factor and benefit reward method and punishment in increase discipline and achievement maha santri. Study this use method study field /field research with analysis descriptive qualitative , data sources used that is primary data sources and secondary data sources, data collection with to - Use technique observation , interview and documentation and use technique analysis that is data collection , reduction data, data presentation and withdrawal conclusion, source. Results study show that implementation reward method and punishment applied corresponding with regulation existing -will but rewards given very limited and only given one year very in a activity gebyar ma'had, meanwhile punishment given by administrator ma'had so that still many offending maha santri, factor from implementation reward method this that is maha santri as well as benefit from implementation reward method this can add spirit study , learn for responsible answer, as well get used to maha santri train discipline value time and obey to regulations.